Enhancing Secondary Students’ Reading Comprehension Through Local Culture-Based Website: A Classroom Action Research - Agustiana, Vina; Endang; Wulan; Muhammad; Roger (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study investigates the impact of integrating local culture-based website applications on improving the reading comprehension skills of ninth-grade students. Method: Conducted as classroom action research, the study involved 114 students and one English teacher as a collaborator. Over five meetings, students engaged with culturally relevant texts designed to enhance their comprehension, vocabulary, and grammar skills. The research included a pre-test, three treatment sessions using the website application, and a post-test, followed by a questionnaire on students' perceptions of the application. Results: The findings show that the average post-test score rising from 55.6 to 73.4. The decrease in the standard deviation from 12.8 to 9.5 suggests a reduction in performance disparities. A paired sample t-test confirmed the statistical significance of these gains (t(114) = 12.67, p < 0.001), and the large effect size (Cohen’s d = 1.62) indicates a substantial impact of the intervention. The students' responses to the questionnaire reflected a positive attitude toward the use of the application, highlighting its effectiveness and cultural relevance. Novelty: These results suggest that incorporating local cultural content into educational tools can significantly enhance student engagement and learning outcomes.